MASALAH KEPECAHAN KAYU DALAM PENEBANGAN DI HUTAN JATI - Wesman Endom; Maman Mansyur (Pusat Penelitian dan Pengembangan Hasil Hutan, 1991)
This preliminary research. was conducted with the aim of gathering uarious felling aspects in teak forests (Tectona grandia LF), which will be used for desining a practical, simple, and cheap equipment to reduce log split during felilng operation.it is found in the field that the deviation of falling direction in conventional method wa larger than that in mechanical method. An average stump height Was still high and therefore, needs improvement. This will increase the volume of wood and income of the feller. Therefore, appropriate control and counselling of fellers are required.The secondary data showed that log splits may occur at the bottom, midle and top of tree felled. In Songgom (53 tree samples), the split occured : 18.9% at the bottom, 67.9% at the midle and 13.2% at the top. In cipeundeuy (50 trees samples), the figures were 6% at the bottom, 46% at the midle and 48% at the top.